Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.18553/jmcp.2017.23.4.446
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diabetes Treatment-Related Attributes on Costs to Type 2 Diabetes Patients in a Real-World Population

Abstract: Funding from Sanofi supported this study. Tong was an employee of ProUnlimited, under contract with Sanofi during the time of the study. Kitio-Dschassi was a Sanofi employee at time of the analysis. Meng, Casciano, Stern, and Gultyaev are employees of LASER Analytica, which received research funds from Sanofi to conduct this database analysis. Lee was an employee at LASER Analytica at the time of the analysis and has received grants from Sanofi. This manuscript was presented as a poster at the American Diabete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…Ourresults are supported by data from other authors . Heald et al, using available data from a large number of general practitioners (GP) in England, looked at how medication prescription and other factors influence outcomes in their T2D population .…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Ourresults are supported by data from other authors . Heald et al, using available data from a large number of general practitioners (GP) in England, looked at how medication prescription and other factors influence outcomes in their T2D population .…”
Section: Discussionsupporting
confidence: 85%
“…Ourresults are supported by data from other authors. 14 control, and also found both GP delivering increased glycaemic control (≤7.5%) and those with a lower number of patients at glycaemic risk (patients with HbA1c > 10%) was spending less in their overall prescribing costs for each patient with T2D. 22 Furthermore, Oglesby et al also reported a significant increase in the annual diabetes-related costs from US$1505 in patients with…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this scenario, all-cause trial-based use of resources such as ambulances, emergency room visits, and hospitalisation were implemented. Among intensive insulin users it is not possible to establish whether resource use is disease-specific due to older age and increase in comorbidities and complications, 46 48 and thus all-cause resource use is appropriate for scenario evaluation. In the event that these differences were driven by hypoglycaemic events, the assigned hypoglycaemic event costs were removed from the model to avoid potential double-counting.…”
Section: Analysesmentioning
confidence: 99%
“…3 Hypoglycaemia also carries an economic burden, impacting patient productivity and disease management and utilising valuable healthcare resources. 4 According to a recent meta-analysis, hypoglycaemia is prevalent among patients with type 2 diabetes mellitus (T2DM), thus necessitating an individualised approach to treatment and patient education. 5 The Canadian Hypoglycaemia Assessment Tool Program revealed high rates of hypoglycaemia among insulin-treated patients; the researchers advocated for the identification of high-risk insulin-treated patients in order to reduce the incidence of hypoglycaemia in this patient group.…”
mentioning
confidence: 99%